Identifying gene actions to rice yield and its components traits under both normal and drought conditions - Gaballah, Mahmoud M. (Acta agriculturae Slovenica, 2025)
Eight rice genotypes were selected to conduct all crosses in diallel Method 2 Model 1 design to generate genotypes tolerance to drought stress with high yield potential. The parents Giza179 and Sakha 108 and the crosses UYR 3472 × GZ10739 and GZ10487 × Giza179 reported the highest mean values of the grain yield plant-1 under drought conditions. Two and twelve hybrids revealed desirable highly and highly significant positive heterotic effects as a deviation over mid parent, one hybrid obtained significant positive heterotic over betterparent under natural condition. Regarding the grain yield plant-1, four and six parents showed desirable significant and highly significant positive general combing ability effects under either natural and drought conditions, respectively. Five and thirteen hybrids showed desirable significant and highly significant positive specific combining ability effects under both natural and drought conditions, respectively regarding grain yield plant-1. The high significant and positive associated among grain yield and days to heading, relative water content, number of panicles plant-1, thousand grain mass and water use efficiency for both natural and drought environments. The crosses GZ10739 × WAB 638-1, GZ10739 × IRAT112 and WAB 638-1 × IRAT 112 had superior in most agronomic traits at drought condition.
Keywords: combing ability; correlation; drought; dvodimezionalna barvna predstavitev podatkov; heatmap; heterosis; heteroza; korelacija; sposobnost kombinacije; suša